Effect of the neurokinin 3 receptor antagonist fezolinetant on patient-reported outcomes in postmenopausal women with vasomotor symptoms: results of a randomized, placebo-controlled, double-blind, dose-ranging study (VESTA). Issue 12 (December 2020) - Santoro, Nanette; Waldbaum, Arthur; Lederman, Samuel; Kroll, Robin; Fraser, Graeme L.; Lademacher, Christopher; Skillern, Laurence; Young, James; Ramael, Steven
Abstract: Objective: In the primary analysis of the phase 2b VESTA study, oral fezolinetant reduced frequency and severity of menopausal vasomotor symptoms (VMS) compared with placebo. This secondary analysis evaluates effects of fezolinetant on responder rates and patient-reported outcomes (PROs). Methods: In this 12-week, double-blind study, postmenopausal women with moderate/severe VMS were randomized to fezolinetant 15, 30, 60, or 90 mg BID or 30, 60, or 120 mg QD or placebo. Proportion of responders was based on reductions in VMS from daily diary records. P values for comparisons between active treatment and placebo were calculated using logistic regression. Changes from baseline in PROs (Menopause-Specific Quality of Life questionnaire, Hot Flash-Related Daily Interference Scale, Greene Climacteric Scale) were conducted using a mixed model for repeated measurements and compared post hoc with published minimally important differences (MIDs). Results: Of 356 women randomized, 352 were treated and analyzed. A greater proportion of women receiving fezolinetant versus placebo met definitions of response at week 12. For all doses, mean changes from baseline in Menopause-Specific Quality of Life questionnaire VMS scores exceeded the MID (1.2) at weeks 4 (placebo: −1.8; fezolinetant: range, −1.9 to −3.6) and 12 (placebo: −2.3; fezolinetant: range, −2.9 to −4.4). Mean changes in Hot Flash-Related Daily Interference Scale at weeks 4 (placebo: −2.2; fezolinetant: range, −2.5 to −3.8) and 12 (placebo: −2.9; fezolinetant: range, −3.3 to −4.3) exceeded the MID (1.76). Greene Climacteric Scale-VMS domain scores improved for most fezolinetant doses versus placebo (week 4, placebo: −1.7; fezolinetant: range, −2.1 to −3.3; week 12, placebo: −2.1; fezolinetant: range, −2.7 to −3.6). Conclusions: Oral fezolinetant was associated with higher responder rates than placebo and larger improvements in QoL and other PRO measures, including a reduction in VMS-related interference with daily life. Abstract : Supplemental Digital Content is available in the text